Case report: Heterogenous SMARCA4-deficient thoracic non-small cell lung carcinoma with various responses to nivolumab - Lin, Yun-Tzu; Li, Chien-Feng; Wu, Hung-Chang; Jan, Yi-Hua; Kuo, Yu-Hsuan (Frontiers in Immunology, 2023)
SMARCA4-deficient non-small cell carcinoma is an aggressive neoplasm with poor outcome. Several studies have highlighted its immunochemistry, pathophysiology, and underlying mechanisms, but studies of its definite treatment are few. Here, we report on a 69-year-old male with heterogenous pathological presentations of SMARCA4-deficient non-small cell carcinoma. He initially presented with neck lymphadenopathies. Immunohistochemistry staining and genomic profiling confirmed the diagnosis of SMARCA4-deficient non-small cell carcinoma. The patient responded well to immune checkpoint inhibitors with nivolumab. However, new lesions with various pathological presentations and various responses to nivolumab appeared during the treatment course. The patient survived more than 3 years from initial diagnosis. This case shows the efficacy of nivolumab to treat SMARCA4-deficient non-small cell lung carcinoma.